2017
DOI: 10.3233/jad-160954
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Peripheral BDNF Promoter Methylation Predicts Conversion from Amnestic Mild Cognitive Impairment to Alzheimer’s Disease: A 5-Year Longitudinal Study

Abstract: Epigenetic aberrations have been identified as biomarkers to predict the risk of Alzheimer's disease (AD). This study aimed to evaluate whether altered DNA methylation status of BDNF promoter could be used as potential epigenetic biomarkers for predicting the progression from amnestic mild cognitive impairment (aMCI) to AD. A total of 506 aMCI patients and 728 cognitively normal controls were recruited in the cross-sectional analyses. Patients (n = 458) from aMCI cohort were classified into two groups after 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…The study of diagnosis and treatment of senile dementia in Hebei Province; URL: http://www.chictr.org.cn/showproj.aspx?proj=8194; Registration number: ChiCTR‐RRC‐11001345. We recruited 71 patients with aMCI and 69 normal controls from our previous cross‐sectional cohort study of aMCI in Hebei province (Xie, Liu, Jiang, Liu, et al, ; Xie, Liu, Liu, Jiang, et al, ; Xie, Xu, Liu, Liu, et al, ). All subjects were aged 60 years and older, and aMCI and controls were matched for age and gender.…”
Section: Methodsmentioning
confidence: 99%
“…The study of diagnosis and treatment of senile dementia in Hebei Province; URL: http://www.chictr.org.cn/showproj.aspx?proj=8194; Registration number: ChiCTR‐RRC‐11001345. We recruited 71 patients with aMCI and 69 normal controls from our previous cross‐sectional cohort study of aMCI in Hebei province (Xie, Liu, Jiang, Liu, et al, ; Xie, Liu, Liu, Jiang, et al, ; Xie, Xu, Liu, Liu, et al, ). All subjects were aged 60 years and older, and aMCI and controls were matched for age and gender.…”
Section: Methodsmentioning
confidence: 99%
“…For the initial analysis, both HD and PM cases were combined to increase sample size and statistical power. We focused on 12 CpG sites in promoter IV of the BDNF gene (Figure 3) as this region has been previously reported as differentially methylated in Alzheimer's disease and other neurological conditions (Rao et al, 2012;Ikegame et al, 2013;Januar et al, 2015;Kang et al, 2015;Xie et al, 2017). The mean methylation levels for each CpG tested is shown in Figure 4).…”
Section: Dna Methylation Alterations At Bdnf Promoter IVmentioning
confidence: 99%
“…With regards to markers of BDNF gene activity, analyses have focused on DNA methylation of the BDNF promoter in various neurological disorders. Specifically, studies have demonstrated changes in DNA methylation at the BDNF promoter in blood samples from patients with Alzheimer's disease (AD) (Rao et al, 2012;Xie et al, 2017), major depression (Januar et al, 2015;Kang et al, 2015) and schizophrenia (Ikegame et al, 2013). Such studies have suggested that BDNF promoter methylation might be a useful peripheral biomarker of disease symptoms observed in these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To check the effect of the p.Arg190His and p.Arg190Cys mutations on AT‐Hook binding at the promoter region of a target gene, we performed EMSA assays with unmethylated 148 bp double stranded DNA sequence from the BDNF promoter IV (NCBI accession KX964617), as described above and elsewhere (Xie et al., ). All experiments were conducted with 120 ng of PCR‐amplified gel‐purified product with protein concentrations 25, 50, 75, and 100 μM (Figure A–D).…”
Section: Resultsmentioning
confidence: 99%
“…Methods). 120 nM of a 65 bp double stranded probe with a single AT‐rich motif (see below), and 120 ng of 148 bp double stranded sequence BDNF promoter IV (NCBI accession KX964617) (Xie et al., ) were used in the EMSA reactions. After annealing, the samples were run on PAGE, and gels were post‐stained with Invitrogen™ SYBR™ Safe DNA Gel Stain and imaged under BioRad's gel documentation system to detect DNA.…”
Section: Methodsmentioning
confidence: 99%